Inheritance of illegitimate children who are recognized as legitimate and which are not recognized as legitimate - Nayla Nazmi Fazira; Nikmatul Husna; Fauzan Habib Harianja; Muhammad Fahmi Aulia Saragih Turnip; Muhammad Rafly Lubis (ISNU Sumatera Utara, 2025)
Through marriage, it is hoped that offspring, namely children, will be born. However, children are not always born from a legal marriage; many phenomena occur in society where children are born outside of marriage. This study examines the position of children outside of marriage in inheritance according to the Civil Code. The research method used is normative juridical, namely reviewing laws and regulations and literature studies. The results of the discussion in this study are that illegitimate children who are recognized according to the Law can inherit from their parents who acknowledge them and also from their parents' blood relatives, however, in terms of inheriting from their parents' blood relatives, the possibility for these illegitimate children is very small. The Constitutional Court Decision Number 46/PUU-VIII/2010, which is also part of legal reform, so that the child also has a legal relationship with his biological father if it can be proven based on scientific knowledge, technology and/or other evidence according to law. Recognition of an illegitimate child is very important for a father to do in order to create a civil relationship between the child and his father, while for the mother, according to Article 282 paragraph 2 of the Civil Code, which states that even a daughter who is not yet an adult is allowed to acknowledge her illegitimate child.